A long-term investigation of the variation in leaf wax n-alkanes responding to climate on Dongling Mountain, north China. (10th August 2021) - Shi, Minrui; Han, Jiamao; Wang, Guoan; Wang, Jia; Han, Yaowen; Cui, Linlin
Abstract: Long chain n- alkanes of leaf waxes are widely used in paleoclimatic reconstructions. The application of these proxies depends on profound understandings gained from studies of the relationship between climatic factors and long chain n- alkanes in living plants. However, a lot of uncertainties still exist in the relationship due to the interactions among climatic factors, geographical and topographical factors, and phylogeny. In addition, unrealistic or inaccurate climatic data also introduce errors. To evaluate the effect of climate with minimized interfering factors, we conducted long-term measurements of leaf wax n- alkanes of the plants growing on Dongling Mountain, north China from 2004 to 2019, where a meterological observatory is located. On the whole, total n- alkane concentration (Σalk) was positively correlated mean annual precipitation (MAP); average chain length (ACL) was negatively related to MAP; carbon preference index (CPI) had poor correlations with all climate factors. Compared with Σalk, ACL is a better indicator that reflects annual precipitation. The coefficient of ACL vs. MAP is 0.0015/mm. However, MAP accounted for only 40% of the variability in the year-averaged ACL of all plants together due to the significant interspecific differences in the response of leaf wax n- alkane distribution to climatic parameters; thus, ACL should be employed in parallel with other proxies to quantitatively reconstruct paleoprecipitation. We conducted a sample reconstruction of paleoprecipitation using ACL records preserved in the annually laminated sediments of Maar Lake Twintaung, Myanmar. The results of reconstruction using ACL are completely consistent with the results of reconstruction using carbon isotope ratios of n- alkanes, and are highly consistent with historical documents.